Evaluation of the Income Stabilisation Tool in Polish Agriculture - Marietta JANOWICZ-LOMOTT (Communications of International Proceedings, 2021)
We can observe the modernization of Common Agricultural Policy which is aimed at reduction of resources for direct subsidies and their transfer into development of rural areas, in particular management of farm household under risk conditions in the last years . Therefore, in 2013, a new risk management instrument was introduced - Income Stabilization Tool. The objective of IST is securing against income loss without specifying the causes of said loss (which would mean inclusion of factors that have not been subject to market insurance so far). Proposed by the Commission income stabilization tools is new and therefore there is a relatively small number of theoretical or empirical studies. It is worth highlighting that they concentrated mainly on evaluation of IST, specification of beneficiaries in farming populations as well as the need to create proper insurance policy. Having that in mind, a research objective was formulated - to investigate the potential of IST in farm households in Poland. In the paper Author estimated claims from IST, evaluated of minimum level of net premium in Poland on the basis of data from FADN. As highlighted in conclusions, a key element decisive for attractiveness of income stabilization tools is engagement of resources from Common Agricultural Policy. Without them they may become unattractive (mainly due to price factor) for farm households in Poland despite the fact that they play the role of a farmer's income stabilizer.
Keywords: Risk Management In Agriculture; Income Risk; Income Stabilisation; CAP